Embryology and seed development of Paepalanthus sect. Actinocephalus (Koern.) Ruhland (Eriocaulaceae) - Scatena, V. L.; Bouman, F. (Georg Thieme Verlag Kg, 2001)
The embryology and seed structure of Paepalanthus sect. Actinocephalus species were studied. The embryological and structural seed characters fit well with those of the other commelinaceous families. Within the Commelinales sensu Dahlgren, Eriocaulaceae and Xyridaceae represent two embryologically close families. In Paepalanthus sect. Actinocephalus the ovule is orthotropus, bitegmic, and tenuicellate with a micropyle formed by the inner integument. The seeds are endotestal. The outer cell layer of the testa and the outer periclinal wall of the endotesta disintegrate during development. The endotegmen is tanniniferous. The outer layer of the tegmen becomes compressed and is no longer recognizable in the mature seed. The seeds are operculate.
Keywords: Paepalanthus sect. Actinocephalus; ovule; embryology; seed development